"We": conceptual semantics, linguistic typology and social cognition. (January 2021) - Goddard, Cliff; Wierzbicka, Anna
Abstract: This paper explores "we-words" in the languages of the world, using the NSM method of semantic analysis. A simply phrased, cross-translatable explication for English 'we' [1pl] is proposed, suitable also for other languages with a single we-word. At the same time, it is argued that English 'we' co-lexicalises a second distinct meaning "we two" [1du], and that the same goes for other languages with a single we-word. The two explications are identical, except for being based on ALL and TWO, respectively. Both explications involve components of "I-inclusion" (roughly, 'I am one of them') and "subjective identification" (roughly, 'I'm thinking about them all in the same way'). It is argued, furthermore, that both meanings ("we-all" and "we-two") are likely to be found in all languages. To establish this, one has to take account of languages which manifest the "inclusive/exclusive" distinction. For such languages, evidence suggests that one of the two we-words contains a semantic component of "you-inclusion", while the other is semantically unmarked. Languages whose "we words" encode kinship relations are also briefly considered. The analysis has implications for the typology of pronoun systems, for theorising about human social cognition, and for the lexical semantics of key social concepts. Highlights: Proposes a simple, cross-translatable paraphrase for English 'we' [1pl]. Argues that languages with a single "we word" co-lexicalise distinct dual and plural meanings. Proposes a new interpretation of the "inclusive/exclusive" distinction. Proposes explications for "we words" which encode kinship, as well as person/number. Argues that 'we' is a universal element in human social cognition.